2020
DOI: 10.1007/s12325-020-01525-5
|View full text |Cite
|
Sign up to set email alerts
|

Dorzolamide/Timolol Fixed Combination: Learning from the Past and Looking Toward the Future

Abstract: The key clinical attributes of preserved dorzolamide/timolol fixed combination (DTFC) and the emerging potential of preservative-free (PF) DTFC are reviewed with published evidence and clinical experience. The indications and role of DTFC in current glaucoma management are critically discussed. Preserved DTFC became the first intraocular pressure (IOP)-lowering fixed combination (FC) approved by the US Food and Drug Administration (FDA) and remains one of most commonly used medications worldwide. The pharmacol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 190 publications
(253 reference statements)
1
13
0
Order By: Relevance
“…DzT-FC (fixed combination of Timolol 0.5% and Dorzolamide 2%) was the first IOP-lowering fixed combination approved by the US Food and Drug Administration (FDA) in the treatment of POAG and NTG ( Konstas et al, 2021 ). PF-DzT-FC 1 (preservative-free fixed combination of Timolol 0.5% and Dorzolamide 2%) and PF-DzT-FC 2 (preservative-free fixed combination of Timolol 0.5% and Dorzolamide 1%) have also been launched in the market in recent year.…”
Section: Topical Fixed Combination Of Two Agentsmentioning
confidence: 99%
“…DzT-FC (fixed combination of Timolol 0.5% and Dorzolamide 2%) was the first IOP-lowering fixed combination approved by the US Food and Drug Administration (FDA) in the treatment of POAG and NTG ( Konstas et al, 2021 ). PF-DzT-FC 1 (preservative-free fixed combination of Timolol 0.5% and Dorzolamide 2%) and PF-DzT-FC 2 (preservative-free fixed combination of Timolol 0.5% and Dorzolamide 1%) have also been launched in the market in recent year.…”
Section: Topical Fixed Combination Of Two Agentsmentioning
confidence: 99%
“…This study compared two formulations of PF eye drops-tafluprost and dorzolamide/ timolol-with P-latanoprost eye drops, which contain the preservative BAK (0.2 mg/mL). In addition to the fact that BAK is a known cause of corneal toxicities [13,15,17,20,21], chronic, low-grade inflammation of the ocular surface associated with BAK use, which is a risk factor for an increased incidence of AEs, lower tolerability, therapy failure, increased scarring, and subsequent filtration surgery failure, can occur with the long-term use of IOP-lowering therapies [31]. Consequently, the development of PF eye drops which can avoid the toxic effects associated with preservative-containing medications, may signal the way forward for lifelong IOP-lowering therapy [31].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the fact that BAK is a known cause of corneal toxicities [13,15,17,20,21], chronic, low-grade inflammation of the ocular surface associated with BAK use, which is a risk factor for an increased incidence of AEs, lower tolerability, therapy failure, increased scarring, and subsequent filtration surgery failure, can occur with the long-term use of IOP-lowering therapies [31]. Consequently, the development of PF eye drops which can avoid the toxic effects associated with preservative-containing medications, may signal the way forward for lifelong IOP-lowering therapy [31]. According to previous in vitro and in vivo confocal microscopy studies, preservatives commonly contained in PGAs can potentially adversely affect meibomian gland function leading to further exaggeration of the risk for ocular surface dysfunction and, in that context, Guo et al recently reported that diquafosol can circumvent this effect on meibomian gland dysfunction in patients treated with preserved PGAs comparable to being treated with preservative-free PGAs [32].…”
Section: Discussionmentioning
confidence: 99%
“…[ 22 23 24 ] A recently published review of literature suggests ample evidence with the use of dorzolamide–timolol fixed combination as initial therapy to promptly lower significantly high IOP in the presence of significant damage and particularly so in glaucoma with alarming 24-h IOP characteristics. [ 25 ] A recent study conducted by Dixit et al . [ 26 ] also showed >30% reduction in IOP with fixed combination of brinzolamide and timolol eye drops and no side effects, thereby supporting this drug as primary monotherapy in treatment of POAG.…”
Section: Discussionmentioning
confidence: 99%